Research on Echinoderms in Latin America V - Granja-Fernández, Rebeca (2021)
It is a pleasure for us to present this compendium that represents the sixth product of publications of the Iberoamerican Echinoderm Network (RIE), corresponding to 40 scientific papers presented at the Fourth Latin American Conference of Echinoderms, held from November 10th to 15th 2019 in the city of La Paz, Baja California Sur, Mexico. These works encompass aspects of echinoderms such as descriptions of new species, taxonomy, lists of species, new distribution records, paleontology, ecology, reproduction, physiology and aquaculture.